PENERAPAN PENILAIAN KINERJA (Performance Assesment) TERHADAP PENDEKATAN PEMBELAJARAN LANGSUNG PADA POKOK BAHASAN LIMIT FUNGSI ALJABAR UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR - Sri Tresnaningsih, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2010)
Classroom action research has been conducted in SMA Negeri 1 Madiun, by implementing performance assessment on the direct instruction method and obtained information that: (a) the activity of the direct instruction model of learning management with the implementation of performance appraisal on the subject of sub-Limit Function Algebra increased in each round. Score in round I of 3.2 with either category, the second round of 3.5 with very good categories, and the third round of 3.7 with very good categories. (B) learning achievement of students in each round of increases that indicated by the classical mastery learning   in the cycle I is 46.7%, on the second cycle  66.7%, and on the third cycle 82.2%, and (c) Ability student performance from the existing four aspects of the rounds I to III all experienced an increase round. In one aspect, the use of tools and materials in round I, II, and III respectively of 71.9%, 87.5% and 93.7%. In the aspect-2 that is observing the phenomenon observed in round I, II, and III respectively of 75.0%, 84.4% and 90.6%. In the aspect-3 that is analyzing the data of observations on the round I, II, and III respectively of 71.9%, 81.2% and 87.5%. In the aspect-4 which concludes the results of the competency test in round I, II and III respectively of 71.9%, 87.5% and 93,7%.